The Importance Of Cross Cultural Understanding and Awareness In English Language Teaching - Ganap, Nindy (Politeknik Pelayaran Sulawesi Utara, 2023)
Interrelated, interconnected and influential describe the relationship between language and culture. So that in the process of learning both languages can not be separated. English as an international language has the potential to be associated with culture because everyone from all over the world from different countries even different cultural backgrounds use it to connect with the outside world. Nowdays, English is everywhere and even learned everywhere. In this connection knowledge and understanding as well as cultural awareness become some of the important things to be integrated into learning. This article aims to reveal the importance of cross-cultural understanding and awareness in teaching English. This article was written using a qualitative research design and collecting data from reference observations from the several sources, which were then discussed in a narrative manner so as to discover the importance of cross-cultural understanding and awareness in teaching English.